Optimization of broccoli microencapsulation process by complex coacervation using response surface methodology. (April 2016) - Sánchez, F.M.; García, F.; Calvo, P.; Bernalte, M.J.; González-Gómez, D.
Abstract: This work is intended to optimize the microencapsulation process of broccoli particles preserving their chemical healthy composition, in terms of chlorophylls and polyphenol contents and antioxidant activity, increasing its chemical stability and hiding the characteristic broccoli odor that might have a negative impact in consumer's acceptance. Thus, the microencapsulated broccoli could be easily added to processed foodstuff increasing their healthy properties without altering their sensory attributes. Experimental design and response surface methodology (RSM) was applied to optimize operating conditions and the variables that affect broccoli microencapsulation. Based on that, the optimum process conditions determined by RSM were as follows: pH value 4.5; broccoli–wall material ratio 50% and concentration of wall material 4%, where the theoretical and practical encapsulation efficiency was 60% and 58%, respectively. Industrial relevance: Nowadays, consumers are increasingly interested in beneficial effects of vegetables on health. In this sense, broccoli has been highly valued for their chemopreventive effects, attributed to its composition in glucosinolates, flavonoids, carotenoids, ascorbic acid and amino acids. All these substances are easily degraded by the action of oxygen, thus reducing their potential health benefit. Microencapsulation process has the advantage of reducing the reactivity to factors such as water, oxygen or light, while reducing evaporation or transmission rate to the outside environment. Highlights: Box–Behnken design is adequate to predict broccoli microencapsulation process. This model allows identifying the variables that more affects the process. The encapsulating agent concentration was the variable that most affects the process. The microencapsulation process allows masking broccoli off odor.